Investigating pupillometry as a novel mechanism for detecting emotional regulation difficulties in individuals with PTSD - Ginton, Lee (Department of Psychiatry and Mental Health, 2018)
Objective: Individuals with posttraumatic stress disorder (PTSD) have been found to exhibit emotional regulation difficulties. However, much remains to be learned about the specific neural mechanisms that underlie such difficulties. This study aimed to use eye tracking to investigate the mechanisms underlying emotional regulation difficulties in individuals with PTSD. Method: A total of 87 trauma-exposed mothers (34 PTSD positive and 53 non-PTSD controls) completed an eye tracking assessment in which pupillary dilation in response to emotionally valenced stimuli was measured. The participants also completed two self-report measures of emotional regulation. Results: The PTSD group exhibited increased pupillary dilation to positively valenced stimuli compared to the trauma-exposed, non-PTSD group. In contrast, there was no difference between the two groups using self-report measures of emotional regulation. Additionally, there were no associations between self-report measures and pupillary response to emotionally valenced stimuli. Conclusion: The findings may reflect impaired parasympathetic nervous system processes in individuals with PTSD. The finding that eye tracking, but not emotional regulation questionnaires, differentiated the groups may reflect the point that self-report measures are biased by an individual's ability and willingness to respond. These findings need to be followed up with additional experiments to delineate parasympathetic and other mechanisms involved in underpinning emotional regulation difficulties in PTSD.